Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.12659/ajcr.926034
|View full text |Cite
|
Sign up to set email alerts
|

A 28-Year-Old Man from India with SARS-Cov-2 and Pulmonary Tuberculosis Co-Infection with Central Nervous System Involvement

Abstract: Patient: Male, 28-year-old Final Diagnosis: COVID-19 • tuberculosis Symptoms: Dizziness • headache • vomiting Medication:— Clinical Procedure: Craniectomy Specialty: Infectious Diseases • Neurology • Pathology Objective: Rare co-existance of disease or pathology Background: Tuberculosis (TB) is a great mimic of central nervous system (CNS) tumors. This mimicry may pose a challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
(21 reference statements)
0
14
0
3
Order By: Relevance
“…Quando solicitados exames de imagem, o principal método utilizado foi a tomografia computadorizada (TC) de tórax que mostrou nos pacientes uma sobreposição geralmente bilateral de achados de ambas as condições, como a árvore em brotamento, cavidades ou consolidações da tuberculose com o padrão em vidro fosco ou espessamento intersticial do COVID-19 (Luciani et al 2020;Motta et al 2020;Sarinoglu et al 2020;Tham, et al 2020;Yao et al 2020). O raio X (RX) de tórax também apresentou achados de ambas as patologias, como cavitações, opacificações e derrame pleural (Ata et al 2020;Sarinoglu et al 2020;Tham, et al 2020;Yousaf et al 2020). Nenhum dos trabalhos analisou se o padrão de imagem da TC ou do RX de tórax dos pacientes coinfectados era mais grave que o de pacientes apenas com COVID-19.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Quando solicitados exames de imagem, o principal método utilizado foi a tomografia computadorizada (TC) de tórax que mostrou nos pacientes uma sobreposição geralmente bilateral de achados de ambas as condições, como a árvore em brotamento, cavidades ou consolidações da tuberculose com o padrão em vidro fosco ou espessamento intersticial do COVID-19 (Luciani et al 2020;Motta et al 2020;Sarinoglu et al 2020;Tham, et al 2020;Yao et al 2020). O raio X (RX) de tórax também apresentou achados de ambas as patologias, como cavitações, opacificações e derrame pleural (Ata et al 2020;Sarinoglu et al 2020;Tham, et al 2020;Yousaf et al 2020). Nenhum dos trabalhos analisou se o padrão de imagem da TC ou do RX de tórax dos pacientes coinfectados era mais grave que o de pacientes apenas com COVID-19.…”
Section: Discussionunclassified
“…Dois autores relataram complicações neurológicas em pacientes coinfectados (Ata et al 2020;Freij et al 2020) que demandaram intervenção neurocirúrgica. A literatura aponta que os coronavírus apresentam potencial neuroinvasivo e mesmo na ausência de coinfecção por TB podem cursar com sintomas neurológicos como cefaleia, tontura, hiposmia e acidente vascular encefálico isquêmico ou hemorrágico (Freij et al, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bacterial coinfection is a common problem in COVID-19 patients (11). During the outbreak of COVID-19, many cases of TB/COVID-19 coinfection were reported (12)(13)(14)(15)(16). Some studies reported death in coinfected patients with TB and COVID-19 (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Calcagno and coworkers reported coinfections with other respiratory pathogens such as Staphylococcus aureus, Morax-Pseudomonas aeruginosa along with S. pneumoniae, S. aureus and Klebsiella pneumoniae were diagnosed. Also, mycobacterium tuberculosis coinfection was observed in COVID-19 patients[41][42][43], although such coinfections reportedly do not frequently occur. Mohamed and coworkers reported multi-triazole resistant Aspergillus fumigates coinfection in respiratory samples and suggested that early diagnosis would help to understand the antifungal therapy to improve the diseases condition[45].…”
mentioning
confidence: 96%